Traumatic dental injuries in the primary dentition and sequelae in the permanent dentition: a 7-year retrospective study - Kominami, Paula Akemi Albuquerque; Costa , Vanessa Polina Pereira; Rezende , Liliana Vicente Melo de Lucas; Garcia, Fernanda Cristina Pimentel; Almeida, Julio César Franco; Takeshita, Eliana Mitsue (Brazilian Dental Science, 2022)
Objective: Traumatic dental injuries (TDIs) affect the aesthetics and function of primary teeth and can cause sequelae in their permanent successors. This study assessed the distribution of TDIs and sequelae in the primary dentition and the respective permanent dentition in children treated at the Dental Trauma Centre in Brazil. Material and Methods: This cross-sectional study was conducted by collecting data from 256 dental records over 7 years. Descriptive statistical analyses and the Fisher exact test were used (p=0.05). Results: Sixty-two patients presented with trauma in the deciduous teeth. TDIs were observed mostly in boys (64.50%) and in the 2 to 4-year age group (44.10%); most injuries occurred from fall from the child’s own height (40.30%) and at home (71.20%). The most common type of trauma was subluxation (22.90%). The most prevalent clinical and radiographic sequelae were mobility (45.60%) and periapical lesion (31.80%), respectively. Regarding the permanent dentition, the most frequent sequela was hypomineralization (33.30%). Conclusion: According to this study, TDIs in deciduous teeth made up 29.24% of all the cases in the Dental Trauma Program. The major type of trauma in children was subluxation, with sequelae in both dentitions. Follow-up after trauma is important to the maintenance of primary dentition and to prevent and treat possible sequelae in the permanent dentition. KEYWORDS Deciduous dentition; Dental health; Injury; Permanent dentition; Sequelae.